2008
DOI: 10.1111/j.1365-313x.2008.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of two glutamine synthetase genes by a single Dof transcription factor

Abstract: SummaryThe PpDof5 transcription factor from maritime pine (Pinus pinaster) is a regulator of the expression of glutamine synthetase (GS) genes in photosynthetic and non-photosynthetic tissues. PpDof5 mRNA is detected almost ubiquitously during pine development with low levels of gene expression in green tissues and much higher levels in roots and lignified shoots. The PpDof5 protein expressed in bacteria binds to oligonucleotide probes containing the AAAG core sequence derived from the promoters of GS1a and GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Although it is unclear to date whether Dof genes are directly involved in nitrogen regulation in Arabidopsis, our results show that several genes involved in ammonium assimilation, nitrate reduction, or transport of nitrate were up-regulated more than 2-fold or down-regulated less than 0.5 fold in some Dof-expressed T87 calli (Table 3). A recent report demonstrated that a Dof transcription factor, PpDof5, differentially (positively or negatively) regulates the expression of two genes encoding cytosolic glutamine synthases (Rueda-López et al 2008). Interestingly, a gene encoding cytosolic glutamine synthase was up-regulated in the DOF16 callus overexpressing AtDof5.4, which is a close relative to PpDof5.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is unclear to date whether Dof genes are directly involved in nitrogen regulation in Arabidopsis, our results show that several genes involved in ammonium assimilation, nitrate reduction, or transport of nitrate were up-regulated more than 2-fold or down-regulated less than 0.5 fold in some Dof-expressed T87 calli (Table 3). A recent report demonstrated that a Dof transcription factor, PpDof5, differentially (positively or negatively) regulates the expression of two genes encoding cytosolic glutamine synthases (Rueda-López et al 2008). Interestingly, a gene encoding cytosolic glutamine synthase was up-regulated in the DOF16 callus overexpressing AtDof5.4, which is a close relative to PpDof5.…”
Section: Resultsmentioning
confidence: 99%
“…Dof proteins are encoded by a multigene family and have been identified in diverse plant taxa ranging from unicellular Chlamydomonas to vascular and nonvascular plants ( Moreno-Risueno et al, 2007a). Dof proteins contain a highly conserved N-terminal Dof domain of 50e52 amino acids, including a single C(2)eC(2) type zinc finger motif, which binds specifically to T/AAAAG-like elements in the promoter of target genes (Yanagisawa, 2002;Rueda-L opez et al, 2008). The Dof TF proteins can also mediate proteineprotein interactions in addition to the DNA-binding activity.…”
Section: Introductionmentioning
confidence: 99%
“…In conifers, the Dof gene family plays a key role in the control of ammonium assimilation for glutamine biosynthesis (Rueda-López et al 2008). Dof genes are directly involved in regulating primary metabolism in maritime pine, as they are involved in primary ammonium assimilation from the soil, a crucial process for tree growth and development (Rueda-López et al 2008), and our results suggest that this may be also the case for Aleppo pine.…”
Section: Association Geneticsmentioning
confidence: 64%